The Impact of Slang Usage on Indonesian from a Sociolinguistic Perspective - Enie Hendrajat; Siti Zahrok; Edi Subali; Dyah Satya Yoga Agustin; Wahyuddin Wahyuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
The use of good and correct Indonesian is reduced due to the emergence of the use of new language vocabulary or what is commonly called slang. Slang is a popular type of informal language, but its adaptability poses difficulties for current natural language processing systems. This study aims to describe the use of Slang by university students in Surabaya and its impact on the use of Indonesian. Data collection used a survey to respondents. The results of the analysis show that Slang is often used by university students in Surabaya. The positive impact of the use of Slang among students is that it makes them more creative in using language that is easier to remember and pronounce. The negative impact decreases the quality of Indonesian language formalism. The use of correct Indonesian is only used in lectures as well as writing articles, papers, and other scientific works.